How to deepen college students' approach to using technologies in T‐O‐IBL? Examining the mediating influence of deep approaches to using technologies between learning factors and higher order thinking skills. (3rd September 2022) - Lu, Kaili; Pang, Feng; Shadiev, Rustam
Abstract: Background: Inquiry‐based learning is a salient instructional approach to cultivate students' higher order thinking skills (HOTS). With the presence and advancement of new technologies, their usage for inquiry learning in university context is increasingly ubiquitous. However, in most circumstances, college students cannot integrate technologies to their inquiry learning in efficient ways or their abilities to use technologies are not good enough. Previous studies found that intrinsic motivation (IM), peer interaction (PI) and classroom connectedness (CC) were key factors to influence students' approaches to using technologies from the personal, behavioural and environmental perspectives. Objectives: This study investigated the influence of these three essential learning factors (IM, PI and CC) on students' HOTS and the mediate influence of deep approach to using technologies (DAUT) between these learning factors and HOTS in the technology‐enhanced open inquiry‐based learning context. Methods: A questionnaire was administered to 80 university students who had studied with the technology‐enhanced open inquiry‐based learning approach. The partial least squares method was employed to investigate the relationships among learning factors, DAUT and HOTS. Results and Conclusions: Results showed that CC and PI were positively directly related to HOTS. DAUT was a significant mediator between two (i.e., IM and PI) of the three learning factors and HOTS. The findings of the study have practical implications for instructors, indicating that they should pay attention to students' IM and PI in deepening their approach to using technologies as well as to improve students' HOTS in technology‐enhanced open inquiry‐based learning. Lay Description: What Is Already Known About This Topic: Inquiry‐based learning is considered to be a salient instructional approach to cultivate students' higher order thinking skills (HOTS). Technologies usage in inquiry learning is ubiquitous in university context. In most cases, college students are not able to integrate technologies in their inquiry learning in effective ways. What This Paper Adds: This paper proposed a research model that explains and predicts the mediating influence of deep approach to using technologies on the association between learning factors and HOTS in the technology‐enhanced open inquiry‐based learning context. The mediating effect of approaches to using technologies between learning factors and HOTS was identified. Two of the three learning factors (peer interaction and classroom connectedness) had direct effect on HOTS. Deep approaches to using technologies variable significantly mediates two of the three learning factors (peer interaction and intrinsic motivation) and HOTS. Implications for Practice or Policy: Instructors should pay attention to students' intrinsic motivation (IM) and peer interaction in order to deepen their approach to using technologies. Instructors should pay particular attention to peer interaction and classroom connectedness when conducting technology‐enhanced open inquiry‐based learning activities to improve college students' HOTS. Students' interest improvement and IM in using technologies, the integration of technologies and open inquiry‐based learning activities could be discussed and decided by both the instructor and students.